2007
DOI: 10.1007/s10522-007-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of iNOS and TNF-α expression by kaempferol via NF-κB inactivation in aged rat gingival tissues

Abstract: The primary objective of this study was to evaluate the ability and mechanism of action of kaempferol, which is contained in extracts from Nelumbo nucifera, a well-known Oriental herb used in traditional medicine, with regard to the inhibition of iNOS and TNF-alpha expression in aged rat gingival tissues. We conducted an investigation into the age-related effects of kaempferol on reactive oxygen species (ROS) and GSH oxidative status in samples of aged gingival tissues. Western blotting was conducted in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…In this study, an elevated TNF-α level induced the expression of iNOS and increased NO concentrations in PHG, which was aggravated by E-arr1 deficiency. Moreover, the pivotal elements of NF-κB, p65, which could enhance iNOS [25,26], was also activated in PHG mucosa, and this was exacerbated by E-arr1 deficiency. These results were consistent with TNF-α regulation of iNOS expression via p65 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an elevated TNF-α level induced the expression of iNOS and increased NO concentrations in PHG, which was aggravated by E-arr1 deficiency. Moreover, the pivotal elements of NF-κB, p65, which could enhance iNOS [25,26], was also activated in PHG mucosa, and this was exacerbated by E-arr1 deficiency. These results were consistent with TNF-α regulation of iNOS expression via p65 activation.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a complex of dimeric subunits that belong to the NF-NB/Rel family: NF-κB1 (p50 and its precursor p105), NF-κB2 (p52 and its precursor p100), p65 (RelA), RelB and c-Rel [24]. As the main functional element, p65 was involved in regulation of various physiological and pathological events, and p65 activation was involved in reperfusion injury and iNOS gene regulation in pancreatic β-cells, gingival tissues, and intestinal cells [19,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our observations are consistent with previous reports, which demonstrated that kaempferol blocked TNFα-induced translocation of the NF-κB subunit p65 from the cytoplasm to the nucleus in mouse primary calvarial osteoblasts (Pang et al, 2006) and downregulate iNOS and TNFα expression via NF-κB inactivation in aged rat gingival tissues . Kim et al (2007) showed the inhibitory effects of kaempferol against the aging process such as inflammation in gingival tissues and demonstrated the underlying molecular mechanisms. We predicted the NF-κB family signal as one putative regulatory network from the epidermal genes regulated differentially by kaempferol using bioinformatic methods and confirmed the prediction with the ELISA-based transcription factor assay.…”
Section: Cellsmentioning
confidence: 98%
“…Mangiferin (C2-β-d -glucopyranosyl-1,3,6,7-tetrahydroxyxanthone) is widely distributed in higher plants, has antioxidant capacity [ 253 ], and reduces the alveolar bone loss of rats with experimental periodontitis [ 29 ]. Kaempferol (3,4,5,7-tetrahydroxyfl avone), a fl avonoid glycoside which is particularly abundant in fruits, vegetables, and beverages such as tea [ 254 ], attenuated the NF-κB nuclear binding activity in rat gingival tissue [ 255 ]. Pycnogenol is a water-soluble mixture of fl avonoid compounds extracted from French maritime pine bark and chewing gum containing this compound minimizes gingival bleeding and plaque formation in humans [ 256 ].…”
Section: Other Flavonoidsmentioning
confidence: 99%